2017
DOI: 10.1093/nar/gkx799
|View full text |Cite
|
Sign up to set email alerts
|

Ritornello: high fidelity control-free chromatin immunoprecipitation peak calling

Abstract: With the advent of next generation high-throughput DNA sequencing technologies, omics experiments have become the mainstay for studying diverse biological effects on a genome wide scale. Chromatin immunoprecipitation (ChIP-seq) is the omics technique that enables genome wide localization of transcription factor (TF) binding or epigenetic modification events. Since the inception of ChIP-seq in 2007, many methods have been developed to infer ChIP-target binding loci from the resultant reads after mapping them to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…DNase-seq data has been shown, if analysed correctly, to contain high resolution "footprints" of transcription factor binding within the open chromatin regions 20 . Similarly, it has been shown that the independent visualisation of the left and right hand reads in a paired end ChIP-seq experiment more precisely localises the bound protein 21 . To provide these highresolution data NGseqBasic plots the distribution of fragment ends which it derives from the aligned sequences.…”
Section: Introduction and Resultsmentioning
confidence: 88%
“…DNase-seq data has been shown, if analysed correctly, to contain high resolution "footprints" of transcription factor binding within the open chromatin regions 20 . Similarly, it has been shown that the independent visualisation of the left and right hand reads in a paired end ChIP-seq experiment more precisely localises the bound protein 21 . To provide these highresolution data NGseqBasic plots the distribution of fragment ends which it derives from the aligned sequences.…”
Section: Introduction and Resultsmentioning
confidence: 88%
“…To ensure identification of all ATAC-seq peaks a combination of the traditional MACS2 approach 106 (v2.0/10 callpeak -B -q 0.01) and digital signal processing with Ritornello 107 (v2.0 default settings) was used. Peak summits from both calls were extended to 500 bp and intersected with bedtools 105 (v2.25.0), and filtered for high ploidy regions in MIG viewer 108 to form peak calls for each cell type (Supplementary Tables 8a-p).…”
Section: Methodsmentioning
confidence: 99%
“…ChIP-seq experiments are performed to identify sites of chromatin modification or protein binding, visualized as peaks. For genome wide analysis, peaks are identified bioinformatically, most commonly with MACS2, though newer methods use digital signal processing (Stanton et al , 2017) and Machine Learning e.g. (Hocking et al , 2017) .…”
Section: Identification Of Chip-seq False Positives With MLVmentioning
confidence: 99%